Lithium iron phosphate positive electrode material and preparation method thereof, positive electrode plate and lithium battery

Through surfactant modification and atomization-fluidization reaction technology, the high resistivity problem caused by the aggregation behavior of lithium iron phosphate positive electrode materials is solved, the easy dispersion and electrochemical performance of the material are improved, and the electrical power of lithium batteries is improved Chemical properties.

CN119230825APending Publication Date: 2024-12-31GUANGDONG BRUNP RECYCLING TECH CO LTD

Patent Information

Application Number
CN202411719695.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Due to its crystal structure, lithium iron phosphate positive electrode material has a lower ion diffusion rate and conductivity, resulting in enhanced agglomeration behavior, affecting the uniformity and electrochemical properties of the material, and thus affecting the electrochemical properties of lithium batteries.

Method used

Through surfactant modification and atomization-fluidization reaction technology, lithium iron phosphate positive electrode material with suitable agglomeration strength is prepared, reducing the agglomeration strength of secondary particles and improving the dispersion and conductivity of the material.

Benefits of technology

The dispersion of lithium iron phosphate positive electrode material is achieved, the resistivity of the electrode sheet is reduced, the uniformity of the slurry and the coating performance are improved, and the electrochemical performance of lithium batteries is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230825A_ABST
    Figure CN119230825A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode plate and a lithium battery, and relates to the technical field of lithium batteries. The agglomeration strength of the lithium iron phosphate positive electrode material provided by the invention is in a proper range, the lithium iron phosphate positive electrode material is easy to disperse in a slurry preparation process, the prepared positive electrode slurry has no obvious granular sensation and good fluidity, and the surface density of a positive electrode piece obtained by coating is uniform, so that the resistivity of the pole piece is relatively low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium battery. Background Art

[0002] Lithium iron phosphate is one of the most widely used cathode active materials. Compared with lithium cobalt oxide and ternary cathode materials, lithium iron phosphate has the advantages of long life and good safety performance. In addition, lithium iron phosphate has 170mAh g -1 Theoretical specific capacity and platform discharge voltage of 3.4V make it have considerable energy density.

[0003] However, due to its crystal structure, lithium iron phosphate cathode materials have a low ion diffusion rate and conductivity. In the prior art, nano-sizing, coating, doping and other modification methods are usually used to improve the Li + Diffusion rate and conductivity, but these measures have caused or affected the agglomeration behavior of lithium iron phosphate positive electrode materials to a certain extent. For example, the smaller the particle size of the positive electrode material and the wider the distribution, the easier it is for the positive electrode material to agglomerate; for example, when the coating layer is a carbon material, if the carbon material is distributed in an island shape on the surface of the active material, the surface roughness of the positive electrode material will increase, thereby enhancing the interaction force between the particles, which is conducive to particle agglomeration; for example, the preparation process has an effect on the surface chemical properties of the obtained lithium iron phosphate positive electrode material, thereby affecting the interaction between the particles. The appearance of agglomerated particles can easily lead to scratches and extremely obvious particles on the lithium iron phosphate positive electrode material during the positive electrode coating process, making the surface density of the electrode sheet uneven and difficult to maintain the uniformity of the positive electrode sheet, thereby affecting the consistency of the battery, and then affecting the electrochemical performance of the battery prepared therefrom.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a lithium iron phosphate positive electrode material and a preparation method thereof, a positive electrode plate and a lithium battery, aiming to obtain an easily dispersible lithium iron phosphate positive electrode material, which is beneficial to reducing the resistivity of the plate.

[0006] The present invention is achieved in that: In a first aspect, the present invention provides a lithium iron phosphate positive electrode material, comprising primary particles and secondary particles formed by agglomeration of the primary particles; The agglomeration strength of the lithium iron phosphate positive electrode material is 35-80 MPa, and the agglomeration strength is obtained by compression test.

[0007] In an optional embodiment, the test process of agglomeration strength is as follows: compressing the positive electrode material powder, recording the pressure and sample height during the compression process, and calculating the relationship curve A between the logarithm of the pressure lnP and the compaction density and the relationship curve a between the pressure P and the compaction density; In an optional embodiment, during the compression process, the pressing head compresses the sample at a uniform speed.

[0008] In an optional embodiment, during the compression process, the compression speed of the pressing head is 1-10 mm / min.

[0009] In an optional embodiment, during the compression process, the compression speed of the pressing head is 1 mm / min.

[0010] The pressure P is calculated by the cross-sectional area of ​​the mold loaded with the sample and the pressure applied by the pressure head, and the compaction density is calculated by the cross-sectional area of ​​the mold loaded with the sample and the sample height and sample mass.

[0011] According to the slope change trend, the relationship curve A and the relationship curve a are divided into segment 1, segment 2 and segment 3. Linear fitting is performed on segment 1 and segment 3 on the relationship curve a to obtain two fitting lines. The pressure corresponding to the intersection of the two fitting lines is P1. Linear fitting is performed on segment 3 on the relationship curve A to obtain line A3, and then a tangent is made on segment 2 at the point x=ln(P1), which is recorded as the tangent line. The pressure corresponding to the intersection of the tangent line and line A3 is the agglomeration strength. The goodness of fit r of each linear fitting is 2 ≥0.95; And / or, the compaction density corresponding to the agglomeration strength of the lithium iron phosphate positive electrode material is 1.8 g / cm 3 -2.7g / cm 3 ; And / or, the tap density of the lithium iron phosphate positive electrode material is 0.7 g / cm 3 -1.2g / cm 3 ; And / or, the lithium iron phosphate positive electrode material comprises a lithium iron phosphate active material and a coating layer coated on the surface of the lithium iron phosphate active material; The general formula of lithium iron phosphate active material is Li 1-x M' x Fe 1-y M y (PO 4-z )D z ; Wherein, M' is selected from at least one of Na and Mg; M is selected from at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; D is selected from at least one of F, S, N and Cl; 0≤x≤0.1, 0≤y≤0.1, 0≤z≤0.1; The coating layer contains carbon, and the mass fraction of carbon in the lithium iron phosphate positive electrode material is less than or equal to 5%.

[0012] In a second aspect, the present invention provides a method for preparing the lithium iron phosphate positive electrode material according to any one of the aforementioned embodiments, comprising: Using a surfactant to modify the surface of ferric phosphate to obtain surface-modified ferric phosphate; The ingredients are prepared according to the chemical composition of the lithium iron phosphate positive electrode material, and the surface-modified iron phosphate is mixed with other raw materials to prepare a lithium iron phosphate precursor; The lithium iron phosphate precursor is calcined.

[0013] In an optional embodiment, the process of preparing the surface-modified iron phosphate comprises: mixing anhydrous iron phosphate and an aqueous surfactant solution, performing solid-liquid separation after ultrasonic treatment to obtain liquid-carrying surface-modified iron phosphate; placing the liquid-carrying surface-modified iron phosphate in a fluidized bed for drying; Wherein, the surfactant is an ionic surfactant, and the concentration of the surfactant aqueous solution is 1g / L-10g / L; the amount of the surfactant aqueous solution corresponding to 1g of anhydrous ferric phosphate is 200mL-500mL; The Dv50 of anhydrous iron phosphate is 1μm-9μm, and (Dv90-Dv10) / Dv50 is 0.9~5; The ultrasonic treatment time is 10 min-60 min, and the ultrasonic frequency is 20 kHz-100 kHz; During the drying process in the fluidized bed, the drying temperature is controlled to be 25° C.-40° C., and the water content of the surface-modified iron phosphate is controlled to be 5wt%-15wt%.

[0014] In an optional embodiment, the process of preparing the lithium iron phosphate precursor includes: in a fluidized bed, a mixed solution formed by a carbon source, a lithium source, an M' source, an M source, and a D source is atomized, mixed with the surface-modified iron phosphate, and dried, and atomization and drying are controlled to be performed alternately; The atomization pressure is controlled to be 0.1MPa-5MPa, and the droplet particle size obtained by atomization is 5μm-50μm; During the drying process, the air flow rate of the fluidized bed is controlled to be 50 mL / min-400 mL / min and the temperature is controlled to be 25°C-40°C.

[0015] In an optional embodiment, the carbon source is selected from at least one of glucose, starch, aqueous phenolic resin, sucrose, cellulose, polyethylene glycol, citric acid, cationic polyacrylamide and anionic polyacrylamide; and / or, the lithium source is selected from at least one of lithium hydroxide, lithium carbonate, lithium phosphate, lithium dihydrogen phosphate and lithium acetate; and / or, the M' source is selected from at least one of magnesium acetate, sodium fluoride, sodium chloride and sodium carbonate; and / or, the D source is selected from at least one of potassium fluoride, sodium fluoride, ammonium fluoride, lithium fluoride, amino acid, thiourea, ammonium sulfide, sodium chloride, ammonium chloride, lithium chloride and urea; and / or, the M source contains at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y, and the M source is selected from at least one of hydroxides, nitrates, hydrochlorides and organic acid salts; and / or, Li in the mixed solution + The concentration of is 0.5M-3M, and the concentration of carbon source is 10g / L-50g / L; And / or, when preparing the ingredients, the ratio of the total molar amount of the iron element and the M element to the molar amount of the lithium element is controlled to be 1: (1.01-1.10).

[0016] In an optional embodiment, during the calcination process, the calcination temperature is controlled to be 550° C.-650° C., and the calcination time is 2 h-6 h; and / or, the calcination atmosphere is an inert atmosphere; And / or, calcination is carried out in a suspension furnace.

[0017] In a third aspect, the present invention provides a positive electrode plate, comprising the lithium iron phosphate positive electrode material of any one of the aforementioned embodiments or the lithium iron phosphate positive electrode material prepared by any one of the preparation methods of the aforementioned embodiments.

[0018] In a fourth aspect, the present invention provides a lithium battery comprising the positive electrode sheet of the aforementioned embodiment.

[0019] The present invention has the following beneficial effects: the agglomeration strength of the lithium iron phosphate positive electrode material provided by the present invention is within an appropriate range, and it is easy to disperse during the slurry preparation process; the prepared positive electrode slurry has no obvious granularity and good fluidity; and the surface density of the positive electrode sheet obtained by coating is uniform, thereby making the resistivity of the sheet lower. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0021] Figure 1The relationship curve A between the logarithm of the pressure lnP and the compaction density and the relationship curve a between the pressure and the compaction density measured by the compression method of the lithium iron phosphate positive electrode material in Example 1; Figure 2 A schematic diagram of a spray-drying device used in an embodiment of the present invention; Figure 3 This is a SEM image of the positive electrode material prepared in Example 1; Figure 4 This is a SEM image of the positive electrode material prepared in Comparative Example 1; Figure 5 TEM test images of Example 1 and Comparative Example 3.

[0022] Icon: 1- atomizing gun; 2- loading plate; 3- air jet hole. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0024] An embodiment of the present invention provides a lithium iron phosphate positive electrode material, including primary particles and secondary particles formed by agglomeration of the primary particles.

[0025] It should be noted that there are generally three types of particle forms in lithium iron phosphate positive electrode material powder: grains, primary particles and secondary particles. Grains refer to single crystals with uniform material structure inside the grains, single phase and no grain boundaries. Primary particles are separated particle monomers, which may have grain boundaries but no pores inside the particles. Primary particles can be composed of one grain or multiple grains. Secondary particles are larger particles formed by primary particles through surface tension or solid bridge action, and have a network of interconnected pores inside. Secondary particles are divided into "hard agglomerates" and "soft agglomerates". "Soft agglomerates" are formed by weaker physical interaction forces such as intermolecular forces and capillary forces, and are easily broken into primary particles; "hard agglomerates" are formed by stronger chemical interaction forces such as solid bond bridges, so they are difficult to break into primary particles.

[0026] The agglomeration strength of the lithium iron phosphate positive electrode material provided by the present invention is 35~80MPa, and the agglomeration strength is obtained by compression test. Agglomeration strength can reflect the difficulty of particle processing of lithium iron phosphate positive electrode material. If the agglomeration strength of the positive electrode material is too large, the positive electrode material is difficult to disperse evenly, and the uniformity of the obtained positive electrode slurry is poor, so that the surface density uniformity is poor, thereby increasing the resistivity of the pole piece; if the agglomeration strength is too small, the viscosity of the positive electrode slurry is too low, which makes the slurry difficult to dry, reduces the drying efficiency of the coating, and also causes problems such as coating cracking, slurry particle agglomeration, and poor surface density consistency, thereby causing anisotropy of conductivity, and then causing the resistivity of the pole piece to increase. The agglomeration strength of the lithium iron phosphate positive electrode material provided by the present invention is in an appropriate range, and it is easy to be separated into dispersed primary particles when preparing the slurry, so the positive electrode slurry prepared by this has no obvious granularity, good fluidity, and the surface density of the positive electrode sheet obtained by coating is uniform, thereby making the resistivity of the pole piece low.

[0027] It should be noted that the compression method refers to the compression of powders. The test method refers to GB / T 11106-2022 "Method for Determining the Strength of Cylindrical Compacts for Metal Powders". Figure 1 For example, the present invention compresses the positive electrode material powder to obtain a relationship curve between the logarithm of the pressure lnP and the compaction density (hereinafter referred to as relationship curve A), and a relationship curve between the pressure P and the compaction density (hereinafter referred to as relationship curve a). Within the measurement range of the present invention, relationship curves A and a are usually composed of three segments; under low pressure, the primary particles and secondary particles in the powder are rearranged, and at this time, the relationship curve a shows that the compaction density increases sharply and linearly with the increase in pressure. Therefore, in this stage, the relationship curve A presents a curve with a small arc (approximately a straight line) that is almost balanced with the horizontal axis, which is recorded as segment 1; as the pressure increases, the secondary particles in the powder disintegrate, and at this time, the relationship curve a shows that the rate of increase of the compaction density with the increase in pressure gradually slows down, rather than being linear. In this stage, the relationship curve A presents a curve with a larger arc than segment 1, which is recorded as segment 2; as the pressure further increases, the secondary particles in the powder disintegrate into primary particles, and at this stage, the primary particles The particles undergo secondary rearrangement. In this stage, the relationship curve a shows that the compaction density increases linearly with the increase of pressure, but the speed is lower than that of segment 1. Therefore, in this stage, a curve with a smaller arc (approximately a straight line, but with a larger slope than segment 1) is presented on the relationship curve A, which is recorded as segment 3; Linear fitting is performed on segments 1 and 3 on the relationship curve a to obtain two fitting lines. The pressure corresponding to the intersection of the two fitting lines is P1; Linear fitting is performed on segment 3 on the relationship curve A to obtain line A3, and then a tangent is made on segment 2 at the point x=ln(P1), which is recorded as the tangent. The pressure corresponding to the intersection of the tangent and line A3 is the agglomeration strength. This intersection reflects the difficulty of secondary particle disintegration and can be used to evaluate the processing performance of lithium iron phosphate positive electrode materials. The goodness of fit r of each linear fit is2 ≥0.95.

[0028] If the pressure measurement range is further increased, the fourth curve (corresponding to the rupture of primary particles) and the fifth curve (corresponding to the rearrangement of ruptured primary particles) will appear until the compaction density approaches the true density of lithium iron phosphate.

[0029] In an optional embodiment, during the compression process, the pressing head compresses the sample at a uniform speed.

[0030] In an optional embodiment, during the compression process, the compression speed of the pressing head is 1-10 mm / min.

[0031] In an optional embodiment, during the compression process, the compression speed of the pressing head is 1 mm / min.

[0032] The present invention compresses the positive electrode material powder, records the pressure and sample height during the compression process, and calculates a relationship curve between the pressure P and the compaction density (relationship curve a), and further takes the logarithm of the pressure P (lnP) to obtain a relationship curve between the logarithm of the pressure lnP and the compaction density (relationship curve A).

[0033] The pressure P is calculated by the cross-sectional area of ​​the mold loaded with the sample and the pressure applied by the pressure head, and the compaction density is calculated by the cross-sectional area of ​​the mold loaded with the sample and the sample height and sample mass.

[0034] In some embodiments, on the relationship curve between the logarithm of pressure and compaction density, the compaction density corresponding to the agglomeration strength of the lithium iron phosphate positive electrode material is 1.8 g / cm 3 -2.7g / cm 3 , such as 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 , 2.7g / cm 3 wait.

[0035] In some embodiments, the tap density of the lithium iron phosphate positive electrode material is tested using a conventional tap density test method. The tap density of the lithium iron phosphate positive electrode material provided by the embodiment of the present invention is 0.7 g / cm 3 -1.2g / cm 3 , such as 0.7g / cm3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 wait.

[0036] Furthermore, the lithium iron phosphate positive electrode material includes a lithium iron phosphate active material and a coating layer coated on the surface of the lithium iron phosphate active material. The introduction of the coating layer (such as a carbon coating layer) is beneficial to improving the conductivity of the positive electrode material. The secondary particles in the lithium iron phosphate positive electrode material may be formed by the agglomeration of separate lithium iron phosphate active material particles, or may be formed by the agglomeration of active materials with a coating layer.

[0037] In some embodiments, the lithium iron phosphate active material has the general formula Li 1-x M' x Fe 1-y M y (PO 4-z )D z ; Wherein, M' is selected from at least one of Na and Mg, and M' can be any one of the above elements or a combination of two elements; M is selected from at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y, and M can be any one or more of the above elements; D is selected from at least one of F, S, N and Cl, and D can be any one or more of the above elements. x, y, z in the general formula satisfy: 0≤x≤0.1, 0≤y≤0.1, 0≤z≤0.1, such as x can be 0.00, 0.01, 0.03, 0.05, 0.08, 0.10, etc.; such as y can be 0.00, 0.01, 0.03, 0.05, 0.08, 0.10, etc.; such as z can be 0.00, 0.01, 0.03, 0.05, 0.08, 0.10, etc.

[0038] In some embodiments, the coating layer contains carbon, and the carbon mass fraction in the lithium iron phosphate positive electrode material is less than or equal to 5%, preferably 1.1%-1.4%, such as 0.1%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 2.0%, 3.0%, 4.0%, 4.5%, etc.

[0039] The present invention also provides a method for preparing a lithium iron phosphate positive electrode material, which minimizes the formation of secondary particles during the preparation process so that the agglomeration strength of the secondary particles in the lithium iron phosphate positive electrode material meets the requirements. Specifically, the preparation can be carried out by the following method, but is not limited to the method provided in the present invention.

[0040] The preparation method provided in the embodiment of the present invention comprises the following steps: S1. Preparation of surface-modified iron phosphate The surface of the ferric phosphate is modified by using a surfactant to obtain the surface-modified ferric phosphate for later use.

[0041] In some embodiments, the process of preparing surface-modified ferric phosphate includes: mixing anhydrous ferric phosphate and a surfactant aqueous solution, performing solid-liquid separation after ultrasonic treatment to obtain liquid-carrying surface-modified ferric phosphate; placing the liquid-carrying surface-modified ferric phosphate in a fluidized bed for drying, removing the solvent during the drying process, and making the surfactant uniformly coated on the surface of the anhydrous ferric phosphate. By drying in a fluidized bed, agglomeration can be further reduced.

[0042] In some embodiments, the surfactant is an ionic surfactant, including anionic surfactants, cationic surfactants, and zwitterionic surfactants. The above commonly used ionic surfactants are all suitable for the preparation method provided by the embodiment of the present invention. In a preferred embodiment, the ionic surfactant is selected from polycarboxylate ammonium salts, such as dispersant SN5027 and Dow TM1618. As a preferred surfactant, polycarboxylate ammonium salts are polymer molecular chains with good film-forming properties. They can be evenly coated on the surface of powder particles through electrostatic adsorption, so that the powder surface is negatively charged, and electrostatic repulsion is used to improve the dispersibility between particles and reduce the degree of agglomeration in subsequent steps. In addition, polycarboxylate ammonium salts can also avoid the introduction of other metal elements.

[0043] Further, the concentration of the surfactant aqueous solution is 1g / L-10g / L, preferably 3g / L-5g / L, specifically 1g / L, 3g / L, 4g / L, 5g / L, 8g / L, 10g / L, etc.; the amount of the surfactant aqueous solution corresponding to 1g of anhydrous ferric phosphate is 200mL-500mL, such as 200mL, 300mL, 400mL, 500mL, etc. The concentration and amount of the surfactant aqueous solution are preferably within the above range to better control the loading amount of the surfactant on the particle surface and achieve a better dispersion effect.

[0044] Furthermore, the Dv50 of anhydrous ferric phosphate is 1 μm-9 μm (such as 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, etc.), preferably 4 μm-8 μm; (Dv90-Dv10) / Dv50 is 0.9~5 (such as 0.9, 1.0, 2.0, 3.0, 4.0, 5.0, etc.), the particle size of anhydrous ferric phosphate is small, and the particle size distribution meets the above range, which can further reduce the agglomeration of particles.

[0045] In some embodiments, the ultrasonic treatment time is 10 min-60 min, such as 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, etc.; the ultrasonic frequency is 20 kHz-100 kHz, preferably 30 kHz-50 kHz, specifically 20 kHz, 30 kHz, 40 kHz, 50 kHz, 80 kHz, 100 kHz, etc.

[0046] In some embodiments, during the drying process in the fluidized bed, the drying temperature is controlled to be 25°C-40°C (e.g., 25°C, 30°C, 35°C, 40°C, etc.), and the moisture content of the surface-modified iron phosphate is controlled to be 5wt%-15wt% (e.g., 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, etc.) by adjusting the drying time. The surface-modified anhydrous iron phosphate is dried at low temperature using a fluidized bed to avoid agglomeration of powder particles.

[0047] S2. Preparation of lithium iron phosphate precursor The ingredients are prepared according to the chemical composition of the lithium iron phosphate positive electrode material, and the surface-modified iron phosphate is mixed with other raw materials to prepare a lithium iron phosphate precursor. The other raw materials include a lithium source, and doping elements and carbon coating materials can also be introduced according to the situation.

[0048] In some embodiments, the process of preparing a lithium iron phosphate precursor includes: in a fluidized bed, a mixed solution formed by a carbon source, a lithium source, an M' source, an M source, and a D source is atomized, mixed with the surface-modified iron phosphate, and dried, and atomization and drying are controlled to be performed alternately. By controlling the alternating atomization and drying, the uniformity of the raw material mixing can be further improved.

[0049] like Figure 2 As shown, the present invention is the first to create an atomization-fluidization reactor. During actual operation, the surface-modified iron phosphate is placed on a carrier plate 2, and an air flow is ejected through the air jet hole 3 below to put the particles in a flowing state. The atomized mixed solution is ejected through the atomizing gun 1 above, so that the lithium source and the carbon source are evenly covered on the surface of the surface-modified iron phosphate, thereby avoiding solid-phase mixing that causes uneven distribution of carbon materials on the surface of lithium iron phosphate after sintering, and avoiding re-agglomeration of the components during drying that causes uneven distribution.

[0050] Specifically, there are multiple air jet holes 3, which are arranged at equal intervals below the carrier plate 2, and the air is discharged evenly; the atomizing gun 1 can be a conventional atomizing nozzle, which is also multiple and arranged at equal intervals above the carrier plate 2. First, a part of the mixed solution is sprayed out by the atomizing gun 1, and then the spraying is stopped and dried at the drying temperature; then, a part of the mixed solution is sprayed out by the atomizing gun 1 again, and then the spraying is stopped and dried at the drying temperature, and the cycle is repeated.

[0051] In some embodiments, the pressure of atomization is controlled to be 0.1MPa-5MPa, such as 0.1MPa, 0.5MPa, 1.0MPa, 2.0MPa, 3.0MPa, 4.0MPa, 5.0MPa, etc.; the particle size of the droplets obtained by atomization is 5μm-50μm, such as 5μm, 10μm, 20μm, 30μm, 40μm, 50μm, etc. During the drying process, the air flow rate of the fluidized bed is controlled to be 50mL / min-400mL / min, such as 50mL / min, 100mL / min, 200mL / min, 300mL / min, 400mL / min, etc., and the drying temperature can be 25°C, 30°C, 35°C, 40°C, etc.

[0052] In some embodiments, the carbon source is selected from at least one of glucose, starch, aqueous phenolic resin, sucrose, cellulose, polyethylene glycol, citric acid, cationic polyacrylamide and anionic polyacrylamide, and the carbon source can be any one or more of the above. The lithium source is selected from at least one of lithium hydroxide, lithium carbonate, lithium phosphate, lithium dihydrogen phosphate and lithium acetate, and the lithium source can be any one or more of the above. The M' source is selected from at least one of magnesium acetate, sodium fluoride, sodium chloride and sodium carbonate, and the M' source can be any one or more of the above. The D source is selected from at least one of potassium fluoride, sodium fluoride, ammonium fluoride, lithium fluoride, amino acids, thiourea, ammonium sulfide, sodium chloride, ammonium chloride, lithium chloride and urea, and the D source can be any one or more of the above.

[0053] In some embodiments, the M source contains at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y. The M source is selected from at least one of hydroxides, nitrates, hydrochlorides and organic acid salts. The M source, based on containing at least one of the above doping elements, can exist in the form of at least one or more of hydroxides, nitrates, hydrochlorides and organic acid salts.

[0054] Furthermore, the Li + The concentration of the carbon source is 0.5M-3M, such as 0.5M, 1.0M, 2.0M, 3.0M, etc.; the concentration of the carbon source is 10g / L-50g / L, such as 10g / L, 20g / L, 30g / L, 40g / L, 50g / L, etc.

[0055] Furthermore, the lithium source is fed in a ratio of n(Li):n(Fe+M) of (1.01-1.1):1 between the total molar amount of the iron element and the M element and the molar amount of the lithium element. Within this range, it is beneficial to further improve the electrochemical performance of the battery prepared by the positive electrode material. Specifically, n(Li):n(Fe+M) can be 1.01:1, 1.03:1, 1.05:1, 1.08:1, 1.10:1, etc. The M' source and the D source can be fed in a molar ratio according to the chemical formula.

[0056] S3. Calcination The lithium iron phosphate precursor is calcined to obtain an easily dispersible lithium iron phosphate positive electrode material.

[0057] In some embodiments, during the calcination process, the calcination temperature is controlled to be 550°C-650°C, and the calcination time is 2h-6h. Within this calcination temperature and time range, the reaction is fully carried out and agglomeration is not easy to occur. Specifically, the calcination temperature can be 550°C, 580°C, 600°C, 620°C, 650°C, etc.; the calcination time can be 2h, 3h, 4h, 5h, 6h, etc.

[0058] Furthermore, the calcination atmosphere may be an inert atmosphere, such as nitrogen, argon, or the like.

[0059] In a preferred embodiment, calcination is performed in a suspension furnace. Using a suspension furnace to sinter the lithium iron phosphate precursor can improve sintering efficiency and avoid agglomeration.

[0060] It should be added that the preparation method provided in the embodiment of the present invention adopts multiple ways to jointly suppress the formation of secondary particles, and uses an atomization-fluidization reactor to mix the materials in liquid phase. The carbon layer coated on the lithium iron phosphate obtained after sintering is evenly distributed, the agglomeration degree of the obtained positive electrode material is low, and the agglomeration strength of the secondary particles is also low, so it has a low agglomeration strength and a high grinding efficiency. It is easy to disperse when preparing the slurry, and the obtained slurry has high fineness, good uniformity, moderate viscosity, and low resistivity of the obtained electrode sheet.

[0061] The embodiment of the present invention also provides a positive electrode plate, including the above-mentioned lithium iron phosphate positive electrode material, and may also include a positive electrode current collector, a positive electrode active coating is formed on at least one surface of the positive electrode current collector, and the lithium iron phosphate positive electrode material is present in the positive electrode active coating as a positive electrode active material. Since the lithium iron phosphate positive electrode material has a low degree of agglomeration, it is easy to disperse when preparing the slurry, and the obtained slurry has high fineness, good uniformity, moderate viscosity, and low resistivity of the obtained plate.

[0062] An embodiment of the present invention further provides a secondary battery, including the above-mentioned positive electrode plate, and may also include a negative electrode plate, an electrolyte, a separator, etc. to form a complete battery structure with good cycle performance.

[0063] Specifically, the specific types of the negative electrode sheet, electrolyte, and separator are not limited. During the charge and discharge process of the secondary battery, active ions are intercalated and removed back and forth between the positive electrode sheet and the negative electrode sheet, and the electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet.

[0064] In other embodiments, the battery may not be in the form of a secondary battery, but may be in the form of a battery module, a battery pack, etc.

[0065] The embodiment of the present invention provides a device, including the above-mentioned secondary battery, battery module or battery pack, which can be used as a power source of the device or as an energy storage unit of the device. The device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0066] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0067] The present invention provides a lithium iron phosphate positive electrode material as shown in Table 1; a positive electrode plate is prepared using the lithium iron phosphate positive electrode material, and the discharge of the positive electrode material slurry and the performance of the prepared positive electrode plate are tested, as shown in Table 2.

[0068] Test method description: (1) The agglomeration strength and compaction density of the positive electrode material were tested by the compression method. The specific steps are as follows: 1±0.01g of positive electrode material was loaded into a steel mold, and the powder in the steel mold was continuously compressed using a Xinsansi CMT5000 universal mechanical testing machine. The movement speed of the pressure head was 1mm / min. The mechanical testing machine automatically recorded the pressure and the displacement of the crossbeam during the compression process, and calculated the compaction density and pressure based on the specifications of the steel mold and the mass of the powder. The relationship curve between the logarithm of pressure lnP and the compaction density (relationship curve A) and the relationship curve between pressure and compaction density (relationship curve a) were obtained.

[0069] Curve analysis: Figure 1As shown, the obtained relationship curve A and relationship curve a are roughly divided into three sections. Origin and other software are used to perform linear fitting on segment 1 and segment 3 on relationship curve a to obtain lines a1 and a3. The pressure corresponding to the intersection of line a1 and line a3 is P1; Line A3 is obtained by linear fitting of segment 3 on relationship curve A, and then a tangent is made at the point x=ln(P1) on segment 2, recorded as the tangent. The pressure corresponding to the intersection of the tangent and line A3 is the agglomeration strength. The compaction density on relationship curve A corresponding to the agglomeration strength is the compaction density corresponding to the agglomeration strength. If the obtained relationship curve a or segment 1 of A is not a smooth curve, the smoothing tool of origin can be used to smooth the curve, and then fit it. The linear fit goodness r 2 ≥0.95.

[0070] (2) Preparation of positive electrode slurry: ① Add the binder PVDF to part of the solvent NMP and stir in a double planetary mixer at an orbital speed of 80 rpm, an autorotation speed of 4500 rpm, and a stirring time of 120 min to obtain a glue solution with a solid content of 7%; ② Add acetylene black to the glue solution and stir at an orbital speed of 80 rpm, an autorotation speed of 4500 rpm, and a stirring time of 60 min to obtain a conductive slurry; ③ Add lithium iron phosphate positive electrode material and the remaining NMP to the conductive slurry at an orbital speed of 80 rpm, an autorotation speed of 6500 rpm, and a stirring time of 90 min, then stir at an autorotation speed of 15 rpm for 30 min to defoam, and obtain a positive electrode slurry with a solid content of 65%. The mass ratio of lithium iron phosphate positive electrode material, acetylene black and PVDF is 96.8:1.2:2, and the average particle size of acetylene black is 40 nm and the specific surface area is 65 m 2 / g.

[0071] Positive electrode sheet preparation: The positive electrode slurry was coated on both sides of an aluminum foil with a thickness of 16 μm, and the surface density of the coated side was controlled to be 25 ± 0.1 mg / cm 3 , and then dried to obtain the positive electrode sheet.

[0072] Viscosity test: Use a viscometer (Lichen Viscometer NDJ-5S) to test, take 100mL of sample, use rotor No. 64, rotate at 60 rpm, start timing from the discharge of the slurry, and test the viscosity of the slurry at discharge (0h) and 4h.

[0073] Fineness: Use a fineness meter (instrument model: Shanghai Chemical Laboratory Equipment Co., Ltd. QXD (0-50 microns) to measure the fineness of the slurry when it is discharged.

[0074] (3) Grinding efficiency (∆Dv10): Weigh the same mass of samples and place them in a planetary ball mill for dry ball milling. After a certain period of time, take samples and measure the particle size using a particle size analyzer, and calculate the particle size change rate ∆Dv10 of Dv10, ∆Dv10=(Dv10-Dv10') / Dv10; where Dv10 refers to the particle size when the cumulative particle size volume distribution based on volume before ball milling reaches 10%, and Dv10' refers to the particle size when the cumulative particle size volume distribution based on volume after ball milling for 30 minutes reaches 10%. Ball milling conditions: frequency of 30Hz, 1mm zirconium oxide beads are used for ball milling, the volume ratio of the amount to the lithium iron phosphate positive electrode material is 1:1, and the rotation speed is 600rpm.

[0075] (4) Electrode resistivity: The electrode resistance is tested using a two-probe test method.

[0076] (5) Particle size and distribution: The particles were tested using a MS3000 laser particle size analyzer.

[0077] (6) Tap density: measured in accordance with GB / T 21354-2008 method for measuring tap density of powder products.

[0078] (7) Chemical composition analysis was performed using PE Avio200 inductively coupled plasma optical emission spectroscopy (ICP-OES).

[0079] Table 1 Composition and parameter test results of positive electrode materials of Examples and Comparative Examples

[0080] Table 2 Test results of positive electrode slurry and positive electrode sheet parameters

[0081] Comprehensive analysis of the data in Table 1 and Table 2 shows that the agglomeration strength of the positive electrode material has a significant effect on its grinding efficiency, slurry performance, and pole piece conductivity. Specifically, the greater the agglomeration strength, the lower the grinding efficiency, the greater the discharge viscosity, and the greater the discharge fineness; but if the agglomeration strength is too large or too small, the stability of the slurry will be poor (the greater the ratio of 4h viscosity to discharge viscosity, the worse the stability) and the resistivity will be large. The reason is that: if the agglomeration strength is too large, it is difficult to disperse the positive electrode material evenly, and it is easy to re-agglomerate after standing and stirring, or the pores of the agglomerates absorb solvents, thereby increasing the viscosity, resulting in poor uniformity of surface density, thereby increasing the resistivity of the pole piece; if the agglomeration strength is too small, the viscosity of the positive electrode slurry is too low, which makes it difficult to dry the slurry, reduces the drying efficiency of the coating, and also causes problems such as coating cracking, slurry particle agglomeration, and poor surface density consistency, which leads to anisotropy of conductivity and then increases the resistivity of the pole piece.

[0082] Example 1 This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: (1) Anhydrous ferric phosphate is dispersed in an aqueous solution of a surfactant, and subjected to ultrasonication and solid-liquid separation to obtain anhydrous ferric phosphate with liquid surface modification.

[0083] Among them, the surfactant is dispersant SN5027, and the concentration of the surfactant aqueous solution is 5g / L; the ratio of anhydrous ferric phosphate to the surfactant aqueous solution is 1g:350mL; the ultrasonic time is 30min, and the ultrasonic frequency is 40kHz; the Dv50 of anhydrous ferric phosphate is 6.2μm, and (Dv90-Dv10) / Dv50 is 2.12.

[0084] (2) placing the surface-modified anhydrous ferric phosphate with liquid in a fluidized bed for drying to obtain surface-modified anhydrous ferric phosphate; The drying temperature was 30° C., and the water content of the obtained surface-modified anhydrous ferric phosphate was 10.02 wt %.

[0085] (3) Use the following Figure 2 The atomization-fluidization reactor shown atomizes a mixed solution containing a coated carbon source and a lithium source, mixes it with a surface-modified anhydrous ferric phosphate and dries it to obtain a lithium iron phosphate precursor; the specific steps are as follows: after the mixed solution containing the coated carbon source and the lithium source is atomized by an atomizing gun 1, it is sprayed from the top of the reactor onto the surface of a carrier plate 2, and the spraying is stopped after 10 seconds. After standing for 10 seconds, the air flow rate of the air jet hole 3 is adjusted so that the surface-modified anhydrous ferric phosphate on the carrier plate is in a suspended state and dried until there is no obvious water stain on its surface, and the suspension is stopped; then the atomizing gun is turned on again for spraying, and the above steps are repeated until the mixed solution is sprayed and there is no obvious water stain on the surface of the particles.

[0086] The carbon source is a mixture of glucose and cationic polyacrylamide in a mass ratio of 1:1, the lithium source is lithium acetate, the solvent is water, and the Li + The concentration of the carbon source is 1.8 M, and the concentration of the carbon source is 25 g / L. The lithium source is fed according to the molar ratio of the iron element to the lithium element n (Li): n (Fe) of 1.01:1.

[0087] The atomization pressure is 2MPa, the droplet particle size obtained by atomization is 5~50μm, and the liquid flow rate of each spraying is 1L / h.

[0088] The air flow rate was 300 mL / min and the drying temperature was 30 °C.

[0089] (4) The lithium iron phosphate precursor is placed in a suspension furnace for calcination to obtain an easily dispersible lithium iron phosphate positive electrode material. The calcination gas atmosphere is an inert atmosphere (nitrogen, the same below), the calcination temperature is 600°C, and the calcination time is 4 hours.

[0090] Example 2 This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: (1) The difference from Example 1 is that the concentration of the aqueous solution of the surfactant is 4 g / L; the ultrasonic time is 60 min; the ultrasonic frequency is 80 kHz; the Dv50 of anhydrous ferric phosphate is 4.2 μm, and (Dv90-Dv10) / Dv50 is 4.84.

[0091] (2) The difference from Example 1 is that the drying temperature is 25° C. and the water content of the obtained surface-modified anhydrous ferric phosphate is 12.05%.

[0092] (3) The difference from Example 1 is that the mixed solution contains a coated carbon source, a lithium source and sodium fluoride, and the feeding amounts of the lithium source and sodium fluoride are according to n (Li): n (Na): n (Fe) of 1.005:0.002:1, wherein n (Fe) refers to the molar amount of iron element in the surface modified anhydrous iron phosphate; the atomization pressure is 5 MPa; the air flow rate is 400 mL / min; the drying temperature is 25 ° C; and the carbon source is a mixture of glucose and polyethylene glycol in a mass ratio of 1:1.

[0093] (4) The difference from Example 1 is that the calcination gas atmosphere is an inert atmosphere, the calcination temperature is 550°C, and the calcination time is 6 hours.

[0094] Example 3 This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: (1) The difference from Example 1 is that the concentration of the aqueous solution of the surfactant is 1 g / L; the ultrasonic time is 10 min; the ultrasonic frequency is 20 kHz; and the ratio of anhydrous ferric phosphate to the aqueous solution of the surfactant is 1 g:500 mL.

[0095] (2) The difference from Example 1 is that the drying temperature is 40° C. and the water content of the obtained surface-modified anhydrous ferric phosphate is 8.08%.

[0096] (3) The difference from Example 1 is that the atomization pressure is 0.5 MPa; the drying temperature is 25°C; and the carbon source is cationic polyacrylamide.

[0097] (4) The difference from Example 1 is that the calcination gas atmosphere is an inert atmosphere, the calcination temperature is 650°C, and the calcination time is 3 hours.

[0098] Example 4 This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: (1) The difference from Example 1 is that the surfactant is dispersant TM1618, the concentration of the aqueous solution of the surfactant is 3 g / L; the frequency of ultrasound is 50 kHz; and the ratio of anhydrous ferric phosphate to the aqueous solution of the surfactant is 1 g:200 mL.

[0099] (2) Same as Example 1.

[0100] (3) The difference from Example 1 is that the carbon source is glucose.

[0101] (4) The difference from Example 1 is that the calcination gas atmosphere is an inert atmosphere, the temperature is 550°C, and the time is 6 hours.

[0102] Example 5 This embodiment provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: (1) The difference from Example 1 is that the Dv50 of anhydrous iron phosphate is 4.2 μm and (Dv90-Dv10) / Dv50 is 4.84.

[0103] (2) Same as Example 1.

[0104] (3) The difference from Example 1 is that the mixed solution contains a coated carbon source, a lithium source, and titanyl sulfate, and the lithium source and titanyl sulfate are added in an amount of n(Li):n(Ti):n(Fe) of 1.02:0.014:0.986, wherein n(Fe) refers to the molar amount of iron in the surface-modified anhydrous iron phosphate; the carbon source is cationic polyacrylamide; (4) The difference from Example 1 is that the calcination gas atmosphere is an inert atmosphere, the calcination temperature is 650°C, and the calcination time is 6 hours.

[0105] Comparative Example 1 This comparative example provides a lithium iron phosphate positive electrode material, and the preparation method includes the following steps: Anhydrous iron phosphate is mixed with a lithium source and a carbon source to obtain a dry material, and ethanol is added as a dispersant to perform ball milling to obtain a wet mixture; the wet mixture is dried and then calcined in a rotary kiln to obtain a lithium iron phosphate material.

[0106] Among them, the Dv50 of anhydrous iron phosphate is 6.2μm, and (Dv90-Dv10) / Dv50 is 2.12; The lithium source is lithium acetate, and the feeding amount of anhydrous iron phosphate and lithium source is 1.01:1. The carbon source is a mixture of glucose and cationic polyacrylamide in a mass ratio of 1:1. The mass of the carbon source is 5.6% of the total mass of anhydrous iron phosphate and lithium source. The amount of ethanol added is 5% of the mass of dry material.

[0107] The ball milling conditions were as follows: the ball milling time was 30 min, the frequency was 30 Hz, 1 mm zirconia beads were used in the ball milling, the volume ratio of the beads to anhydrous ferric phosphate was 1:1, and the rotation speed was 600 rpm.

[0108] The calcination gas atmosphere is an inert atmosphere, the calcination temperature is 600°C, and the calcination time is 8 hours.

[0109] The electron microscope images of the positive electrode materials prepared in Example 1 and Comparative Example 1 are as follows: Figure 3 and Figure 4 It can be seen that the lithium iron phosphate positive electrode material (Comparative Example 1) prepared by conventional methods has more secondary particles than that of Example 1, indicating that the lithium iron phosphate positive electrode material prepared by the preparation method of the present invention has fewer secondary particles.

[0110] Comparative Example 2 This comparative example provides a lithium iron phosphate positive electrode material, and the preparation method is different from that of Example 1 in that no surfactant is added in step (1).

[0111] The following is a further example of the preparation method: The process conditions of the preparation methods of Examples 6 to 13 and Comparative Examples 3 to 5 are shown in Table 3. The agglomeration strength, discharge fineness, and electrode sheet resistivity of the prepared positive electrode materials are shown in Table 3.

[0112] Table 3 Parameter test results of positive electrode materials prepared in Examples and Comparative Examples

[0113] Step (3) of Comparative Example 3 adopts a conventional liquid phase mixing method, specifically: ultrasonically dispersing the surface modified anhydrous iron phosphate in a mixed solution containing a lithium source and a carbon source, ultrasonically dispersing for 20 minutes, and then evaporating the solvent to obtain a lithium iron phosphate precursor.

[0114] From the analysis of Table 3, we can see that: Comparing Example 1 and Example 6, the agglomeration strength of the positive electrode material obtained by using ammonium stearate as the surfactant in step (1) is greater than that of the polycarboxylic acid type surfactant SN5027, indicating that the polycarboxylic acid type surfactant SN5027 has better dispersibility in anhydrous lithium iron phosphate. The reason is that the polymer dispersant has good film-forming properties on the particle surface and has a higher degree of coating on the particles.

[0115] Comparing Example 1 with Examples 7-8, the agglomeration strength of the positive electrode material shows a trend of first decreasing and then increasing as the concentration of the surfactant in step (1) increases. The reason is that when the concentration is too low, the dispersion effect on anhydrous iron phosphate is worse, but when the concentration is too high, more surfactant remains on the surface of the anhydrous iron phosphate particles, resulting in an increase in the carbon content of the lithium iron phosphate positive electrode material, increasing the possibility of uneven coating, and thus increasing the friction between the particles.

[0116] In step (2) of Example 9, the surface-modified anhydrous iron phosphate with liquid is dried in an oven. The resulting lithium iron phosphate positive electrode material has a high agglomeration strength. This is because there is no dispersion effect of the air flow in the fluidized bed, which allows the powder particles to form intermolecular forces during the drying process, causing them to agglomerate.

[0117] Examples 1 and 10-11 show that the atomization pressure in step (3) has an effect on the agglomeration strength of the lithium iron phosphate positive electrode material. Specifically, at the same flow rate, too high a pressure makes the kinetic energy of the atomized droplets greater, and the collision between the particles is violent, which is conducive to agglomeration; too low a pressure makes the atomized droplets unable to quickly adhere to the surface of the surface-modified anhydrous lithium iron phosphate, but diffuses in the device cavity and then slowly adsorbs on the particle surface, resulting in a larger particle size when the droplets adhere, and the coating uniformity is reduced, thereby increasing the friction between the particles, which is ultimately conducive to agglomeration.

[0118] Examples 12-13 show that the concentration of the carbon source affects the carbon content of the product, affects the uniformity of the coating, and ultimately affects the friction between the powder particles of the product, thereby affecting its agglomeration strength.

[0119] Comparative Example 3 shows that when the carbon source and the like are mixed with anhydrous ferric phosphate by conventional liquid phase mixing, the lithium iron phosphate obtained by calcination has a greater degree of agglomeration. This also shows that when the atomization-fluidization method of the present invention is used for mixing, the resulting coating layer is more uniform, which greatly reduces the interaction between the powder particles.

[0120] Comparative Examples 4 and 5 show that the drying temperature has an effect on the agglomeration of the powder, and drying at a low temperature can inhibit the agglomeration between particles.

[0121] TEM images of the positive electrode materials prepared in Example 1 and Comparative Example 3 are shown in the following table. Figure 5 As shown. It can be seen that in Comparative Example 3, the carbon source and the like are mixed with anhydrous iron phosphate by a conventional liquid phase mixing method. From the TEM image, it can be seen that the carbon coating thickness on the surface of the obtained lithium iron phosphate material is uneven, which increases the roughness of the surface of the material particles and increases the friction between the particles, thereby having a higher agglomeration strength.

[0122] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium iron phosphate positive electrode material, characterized in that: It includes primary particles and secondary particles formed by agglomeration of the primary particles; the agglomeration strength of the lithium iron phosphate positive electrode material is 35-80 MPa, and the agglomeration strength is obtained by compression test.

2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: The test process of the agglomeration strength is as follows: compressing the positive electrode material powder, recording the pressure and sample height during the compression process, and calculating the relationship curve A between the logarithm of the pressure lnP and the compaction density and the relationship curve a between the pressure P and the compaction density; According to the slope change trend, the relationship curve A and the relationship curve a are divided into segment 1, segment 2 and segment 3, and linear fitting is performed on segment 1 and segment 3 on the relationship curve a to obtain two fitting lines, and the pressure corresponding to the intersection of the two fitting lines is P1; Linear fitting is performed on segment 3 on the relationship curve A to obtain line A3, and then a tangent is made on segment 2 at the point where x=ln(P1), which is recorded as the tangent; the pressure corresponding to the intersection of the tangent and the line A3 is the agglomeration strength; the goodness of fit r of each linear fit is calculated. 2 ≥0.95; And / or, the compaction density corresponding to the agglomeration strength of the lithium iron phosphate positive electrode material is 1.8 g / cm 3 -2.7g / cm 3 ; And / or, the tap density of the lithium iron phosphate positive electrode material is 0.7 g / cm 3 -1.2g / cm 3 ; And / or, the lithium iron phosphate positive electrode material comprises a lithium iron phosphate active material and a coating layer coated on the surface of the lithium iron phosphate active material; The general formula of the lithium iron phosphate active material is Li 1-x M' x Fe 1-y M y (PO 4-z )D z ; Wherein, M' is selected from at least one of Na and Mg; M is selected from at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y; D is selected from at least one of F, S, N and Cl; 0≤x≤0.1, 0≤y≤0.1, 0≤z≤0.1; The coating layer contains carbon, and the mass fraction of carbon in the lithium iron phosphate positive electrode material is less than or equal to 5%.

3. A method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 2, characterized in that: include: Using a surfactant to modify the surface of ferric phosphate to obtain surface-modified ferric phosphate; According to the chemical composition of the lithium iron phosphate positive electrode material, ingredients are prepared, and the surface-modified iron phosphate is mixed with other raw materials to prepare a lithium iron phosphate precursor; The lithium iron phosphate precursor is calcined.

4. The preparation method according to claim 3, characterized in that: The process of preparing the surface-modified iron phosphate comprises: mixing anhydrous iron phosphate and a surfactant aqueous solution, performing solid-liquid separation after ultrasonic treatment to obtain liquid-carrying surface-modified iron phosphate; placing the liquid-carrying surface-modified iron phosphate in a fluidized bed for drying; Wherein, the surfactant is an ionic surfactant, the concentration of the surfactant aqueous solution is 1g / L-10g / L; 1g of the anhydrous ferric phosphate corresponds to an amount of 200mL-500mL of the surfactant aqueous solution; The Dv50 of the anhydrous ferric phosphate is 1 μm-9 μm, and (Dv90-Dv10) / Dv50 is 0.9-5; The ultrasonic treatment time is 10 min-60 min, and the ultrasonic frequency is 20 kHz-100 kHz; During the drying process in the fluidized bed, the drying temperature is controlled to be 25° C.-40° C., and the water content of the surface-modified iron phosphate is controlled to be 5wt%-15wt%.

5. The preparation method according to claim 3, characterized in that: The process of preparing the lithium iron phosphate precursor comprises: in a fluidized bed, a mixed solution formed by a carbon source, a lithium source, an M' source, an M source, and a D source is atomized, mixed with the surface-modified iron phosphate, and dried, and atomization and drying are controlled to be performed alternately; The atomization pressure is controlled to be 0.1MPa-5MPa, and the droplet particle size obtained by atomization is 5μm-50μm; During the drying process, the air flow rate of the fluidized bed is controlled to be 50 mL / min-400 mL / min and the temperature is controlled to be 25°C-40°C.

6. The preparation method according to claim 5, characterized in that: The carbon source is selected from at least one of glucose, starch, aqueous phenolic resin, sucrose, cellulose, polyethylene glycol, citric acid, cationic polyacrylamide and anionic polyacrylamide; And / or, the lithium source is selected from at least one of lithium hydroxide, lithium carbonate, lithium phosphate, lithium dihydrogen phosphate and lithium acetate; and / or, the M' source is selected from at least one of magnesium acetate, sodium fluoride, sodium chloride and sodium carbonate; And / or, the D source is selected from at least one of potassium fluoride, sodium fluoride, ammonium fluoride, lithium fluoride, amino acid, thiourea, ammonium sulfide, sodium chloride, ammonium chloride, lithium chloride and urea; And / or, the M source contains at least one of Al, Ni, Co, Mn, Ti, La, Ce, Cr, Mo, Ca, Ga, V, Nb, Zr, In, Zn and Y, and the M source is selected from at least one of hydroxide, nitrate, hydrochloride and organic acid salt.

7. The preparation method according to claim 6, characterized in that: The mixed solution contains Li + The concentration of is 0.5M-3M, and the concentration of carbon source is 10g / L-50g / L; And / or, when preparing the ingredients, the ratio of the total molar amount of the iron element and the M element to the molar amount of the lithium element is controlled to be 1: (1.01-1.10).

8. The preparation method according to claim 4, characterized in that: During the calcination process, the calcination temperature is controlled to be 550°C-650°C, and the calcination time is 2h-6h; and / or, the calcination atmosphere is an inert atmosphere; And / or, calcination is carried out in a suspension furnace.

9. A positive electrode sheet, characterized in that: The invention comprises the lithium iron phosphate positive electrode material as described in any one of claims 1 to 2 or the lithium iron phosphate positive electrode material prepared by the preparation method as described in any one of claims 3 to 8.

10. A lithium battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Lithium iron phosphate cathode material, lithium ion battery and preparation method thereof

    CN107834070A

  • Doped lithium iron phosphate as well as preparation method and application thereof

    CN115367725A

  • Composite lithium iron phosphate as well as preparation method and application thereof

    CN118658979A

  • Nanoscale iron phosphate, preparation method therefor and use thereof

    US20240034625A1

Cited By

  • Iron phosphate and preparation method thereof

    CN120943229A

  • Lithium iron phosphate material realized by dual-phase coupling coating and structure regulation and control and application of lithium iron phosphate material

    CN121054659A

  • Nitrogen-doped carbon-coated spherical polycrystalline lithium iron phosphate as well as preparation method and application thereof

    CN121565834A

  • Nitrogen-doped carbon-coated spherical polycrystalline lithium iron phosphate, and preparation method and application thereof

    CN121565834B

  • Lithium-ion secondary battery, battery apparatus, electrical apparatus, preparation method for positive electrode active material, and preparation method for positive electrode plate

    US12706303B1